Some Rock Inscriptions from Gebel el-Silsila. Issue 1 (June 2018) - Nilsson, Maria; Faraman, Ahmed; Said, Abdelmoneim
The subject of this article is a selected group of textual graffiti intended as a preview to a comprehensive hieroglyphic and hieratic corpus of Middle Kingdom rock inscriptions at Gebel el-Silsila currently being prepared for publication. All texts included were incised into the sandstone bedrock and stretched along the so-called Middle Kingdom road as well as along today's main touristic pathway along the New Kingdom cenotaphs, also on the west bank of Gebel el-Silsila. The inscriptions were documented by the current scientific team during the course of several survey seasons (2012–15) and demonstrate various administrative and official titles providing an insight into activity during the Middle Kingdom, which otherwise is difficult to demonstrate archaeologically, i.e. within the physical remains of the ancient quarries. Titles included herein, such as – inspector, – general/mission leader, – seal-bearer of the God and – Royal seal-bearer, indicate an official politico-economic interest in the site, while simultaneously demonstrating religious activity and involvement. The current selection of texts is merely intended as a very brief introduction to the variety of titles and individuals once active at Gebel el-Silsila.